RELATIONS OF SERBIA AND OTHER BALKAN COUNTRIES FROM THE BERLIN CONGRESS TO 1908 (Heritage, 2023)
The Berlin Congress brought significant changes to the political map of Europe. It is important for the Serbian people that two Serbian states gained independence, albeit within modest limits. A large part of the Serbian people remained under Tutrian and Austro-Hungarian rule. The Principality of Serbia has become a center for the gathering of political leaders of the Serbian people outside of Serbia, who are interested in continuing the unification process. There were also many interfering factors, such as the great powers and their conflicting interests, but also the dynastic struggle for dominance of the three Serbian dynasties of Karađorđević, Obrenović and Petrović. Regardless, at the end of the 19th century and the beginning of the 20th century, Serbia's foreign policy was aimed at unifying the Serbian people. The first step was the elimination of Turkey in the Balkans, and that required an alliance with the Greeks and Bulgarians, as well as the favor of some great powers (above all Russia). The great hindering factor in the crushing of Turkey was above all Austria-Hungary and the United Kingdom, each for its own interests. because of this, the path to the creation of the Balkan Alliance was long and arduous. Even the two Serbian countries entered periods of cooling of relations. The issue of territory and demarcation between future allies was also very complex. Serbia had its centuries-old tradition of national and state consciousness in Old Serbia (Vardar region), where the imperial capital, Skopje, and the royal capital Prilep were also located. All historical and national arguments were on the Serbian side, including the creation of the indigenous Serbian Chetnik movement, led by Mickо Krstić, Jovan Stojković Babunski, Jovan Stanojković Dovezenski, and many other Chetnik leaders who came from this land.
Keywords: Serbia, unification, Balkan alliance